2017
DOI: 10.1016/j.bpsc.2017.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Visual Hallucinations Are Characterized by Impaired Sensory Evidence Accumulation: Insights From Hierarchical Drift Diffusion Modeling in Parkinson’s Disease

Abstract: We integrate these results with evidence accumulation and predictive coding models of hallucinations, suggesting that in PD sensory evidence is less informative and may therefore be down-weighted, resulting in overreliance on top-down influences. Considering impaired drift rates as an approximation of reduced sensory precision, our findings provide a novel computational framework to specify impairments in sensory processing that contribute to development of visual hallucinations.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
72
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(82 citation statements)
references
References 71 publications
9
72
1
Order By: Relevance
“…It is possible that by modulating the decision threshold, STN-DBS could alter the bound for evidence accumulation and thus uncertainty in the representation of the reward environment (Herz et al, 2018;Pote et al, 2016). Further work employing drift diffusion modelling to quantify rates of evidence accumulation and decision boundaries after STN-DBS may be illuminating, having previously helped to elucidate the mechanisms underlying hallucinations in Parkinson's disease (O'Callaghan et al, 2017). Further work is also required to determine if the site of stimulation affects the magnitude of changes in uncertainty estimation observed here and specifically if cognitive-associative or sensorimotor regions of the STN are most implicated in these shifts.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that by modulating the decision threshold, STN-DBS could alter the bound for evidence accumulation and thus uncertainty in the representation of the reward environment (Herz et al, 2018;Pote et al, 2016). Further work employing drift diffusion modelling to quantify rates of evidence accumulation and decision boundaries after STN-DBS may be illuminating, having previously helped to elucidate the mechanisms underlying hallucinations in Parkinson's disease (O'Callaghan et al, 2017). Further work is also required to determine if the site of stimulation affects the magnitude of changes in uncertainty estimation observed here and specifically if cognitive-associative or sensorimotor regions of the STN are most implicated in these shifts.…”
Section: Discussionmentioning
confidence: 99%
“…Behavioural performance on the Go/NoGo task was calculated by summing scores for the task conditions, and by modelling latent task variables using the hBayesDM package (hierarchical Bayesian modeling of Decision Making tasks) for R (version 0.5.0 on MacOS High Sierra version 10.13.1) developed by Ahn et al (2017). We used this approach to generate posterior distributions of the parameters characterising task performance to improve the balance of within-subject and between-subject random effects, whilst also taking into account within-subject variability and group-level similarities (O'Callaghan et al, 2017). Full information on the details of the modelling parameters and model fitting and comparison can be found in the Supplementary Material.…”
Section: Computational Modelling: Hbayesdmmentioning
confidence: 99%
“…The orbitofrontal cortex (OFC) process coarse information projected from the visual cortex and provides an "initial guess" of an object's identity (21). Previous work in PD patients with VHs has shown that the accumulation of sensory evidence is slow and inefficient, which may result in an over-reliance on these top-down predictions (22). Importantly, top-down visual processing regions can modulate neural activity in early visual regions, with expected stimuli leading to reduced activity (23).Additionally, activity within the default mode network (DMN), a network involved in mediating endogenous perception, has shown to be increased during a misperception in this patient population (24).…”
mentioning
confidence: 99%
“…Importantly, top-down visual processing regions can modulate neural activity in early visual regions, with expected stimuli leading to reduced activity (23).Additionally, activity within the default mode network (DMN), a network involved in mediating endogenous perception, has shown to be increased during a misperception in this patient population (24). Therefore, VHs may arise when perceptual input is not properly integrated and internally generated images interfere with the perceptual process (22,(25)(26)(27).While functional neuroimaging studies have made significant contributions to our understanding (24,(28)(29)(30)(31), less is known about the involvement of white matter changes in the manifestation of VHs in PD. Experiments using diffusion tensor imaging (DTI) have reported altered white matter integrity in the optic nerve and optic radiation (32) as well as ascending tracts from the cholinergic nucleus basalis of Meynert to parietal and occipital cortical regions (33).…”
mentioning
confidence: 99%
See 1 more Smart Citation